Model-based policymaking or policy-based modelling? How energy models and energy policy interact - Süsser, Diana; Ceglarz, Andrzej; Gaschnig, Hannes; Stavrakas, Vassilis; Flamos, Alexandros; Giannakidis, George; Lilliestam, Johan (Energy Research & Social Science, 2021)
As energy models become more and more powerful, they are increasingly used to support energy policymaking. Although modelling has been used for policy advice for many years, there is little knowledge about how computer-based models actually influence policymaking, and to what extent policymakers influence the modelling process. Here, we empirically investigate (i) whether, how and when models influence the policymaking process, and (ii) whether, how and when policymakers influence the design, use and results of energy modelling. We analysed modelling and policy documents and conducted thirty-two interviews with different stakeholder groups in five different European jurisdictions. We show that models are used and have an impact on policymaking, especially by assessing impacts and supporting target setting, and sometimes by exploring policy options to reach these targets. We also show that policymakers influence models and modellers, especially by affecting data and assumptions, as well as the study scope, and by deciding how the modelling results are used. Hence, energy modelling and policymaking influence each other. In their exploratory mode, models can help investigate policy options and ambitious target setting. However, models can also be instrumentalised to justify already decided policies and targets. Our study implies that greater transparency, including open-source code and open data, and transdisciplinary elements in modelling could increase model legitimacy and impact in policymaking.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Energy modelling; Energy policy; Model-policy-interaction; Policymaking